Pengaruh Struktur Modal, Profitabilitas Dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada Perusahaan Asuransi Di BEI Periode 2019–2022 - Maqbula Arochman; Surenggono Surenggono (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2024)
An insurance company is a company that manages the cash of its customers. An insurance policy is a contract between the policyholder and the insurance company. During the COVID-19 pandemic, the stock market experienced a decline so the value of investment in unit link insurance policies decreased. As a result, few customers experience losses due to the value of insurance investments that become worth zero rupiah. This research aims to analyze the influence of debt-to-equity ratio, return on equity, and dividend payout ratio on the company value of insurance companies on the IDX for the 2019-2022 period. This research uses a purposive sampling method with criteria, namely insurance companies whose shares have actively traded since 2019-2022, and published annual financial reports during the observation period from 2019 to 2022. The total population that meets the criteria is 13 insurance companies with an analysis period of 4 years, the total number of samples is 52. The analysis technique used is the classical assumption test and multiple linear regression analysis. The research results show that the debt-to-equity ratio (DER) has a significant effect on company value (PBV), return on equity (ROE) does not have a significant effect on company value (PBV) and the dividend payout ratio (DPR) has a significant effect on company value (PBV).